A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands - Quaranta, Kimberly L.; Didier, Dominique A.; Long, Douglas J.; Ebert, David A. (Zootaxa, 2006)
A new species of chimaerid belonging to the genus Hydrolagus Gill, 1862 is described from two specimens collected from the Galapagos Islands. This species was taken from depths ranging from 600 – 900 m. Hydrolagus alphus sp. nov. is distinguished from other members of the genus by having proportionately large eyes, dark brown coloration with a noticeable white spot on lateral side, paired fins with a bluish hue and white distal margins, and second dorsal fin with dark anterior and posterior sections separated by a middle portion indented and completely white. This new species is compared to Hydrolagus macrophthalmus, the most similar congener and Hydrolagus mccoskerii the only other known species within this genus to occur in the eastern South Pacific.